Serum IL-6 and IL-10 levels are associated with fatal outcomes in patients with SFTS in China - Xiaoyi Liu; Fan Zhang; Jinping Qiao; Wentao He (Journal of Infection in Developing Countries)
Introduction: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with a high mortality rate and is a public health concern. This study aimed to investigate the associations of serum interleukin 6 (IL-6) and interleukin 10 (IL-10) levels with the prognosis of SFTS patients.